Areas of optimization of operating expenses of a construction enterprise - Yakymchuk, I.; Pokrova, L. (Ways to Improve Construction Efficiency, 2019)
The efficient operation of a construction company depends on the rational use of all kinds of resources, which necessitates the transition to an optimal cost management system. The article discusses the essence, meaning and classification of operating expenses of financial and economic activity of a construction enterprise. The notion of optimization of expenses is defined and the directions of optimization of expenses are adjusted, which allows to use resources of the enterprise more efficiently, to reduce the production cost and maximize profit.